Serum high-sensitive C-reactive protein is a simple indicator for all-cause among individuals with MAFLD - Huang, Jiaofeng; Wang, Mingfang; Wu, Yinlian; Kumar, Rahul; Lin, Su (Frontiers in Physiology, 2022)
High-sensitive C-reactive protein (hs-CRP) is one of the diagnostic components for metabolic (-dysfunction) associated fatty liver disease (MAFLD). This study aimed to explore the relationship between hs-CRP level and 25-year mortality in patients with MAFLD. The study data were from the Third National Health and Nutrition Examination Survey 1988–1994. All participants were followed up until December 2015 and the outcome of each participant was ascertained from National Death Index records. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence interval (CI) of all-cause mortality, cardiovascular-related mortality, and malignancy-related mortality. A total of 4,145 participants with MAFLD were included in final analysis. The median follow-up period was 22.3 years (interquartile range 16.9–24.2). There were 1,610 (38.8%) all-cause deaths. The leading cause of death was malignant neoplasms (365/1610, 22.7%), followed by cardiovascular diseases (342/1610, 21.2%). Of the 4,145 patients with MAFLD, 1,293 (31.2%) had an hs-CRP level greater than 0.5 mg/dL. Those with hs-CRP > 0.5 mg/dL were older, more likely to be female and had greater derangements of metabolic profiles than those with lower hs-CRP. The results of Cox regression analysis showed that hs-CRP ≥ 0.5 mg/dL was an independent risk factor for all-cause mortality (HR=1.394, 95%CI 1.253–1.551), cardiovascular mortality (HR=1.497, 95%CI 1.190–1.885) and malignant neoplasms related mortality (HR=1.290, 95%CI 1.030–1.615) after adjusting for risk factors. This study confirms that hs-CRP is an independent predictive factor of poor prognosis in patients with MAFLD.